Understanding age-based kinetic and kinematic variations in taekwondo`s spinning heel kick - Prock, M.; O`sullivan, D. M.; Panday, S. B. (International Journal of Performance Analysis in Sport, 2025)
This article investigates the effect of age on kinematic and kinetic performance outcomes of the spinning heel kick in taekwondo. A total of 48 athletes were recruited, consisting of 16 students each from middle school, high school, and university. Following a sport-specific warm-up, each participant performed 10 repetitions of the spinning heel kick while their kinematics and kinetics were recorded. A one-way ANOVA was used to analyse the differences between groups, and a simple linear regression model was included to assess the relationship between age and performance outcomes. The results showed significant differences in kicking execution time (middle school < high school, university) and peak kicking velocity (middle school < high school < university) between groups. High school athletes generated the highest normalised ground reaction forces, while university students demonstrated the most effective translation of ground reaction force to maximum kicking speed. Regression analysis revealed age to be a significant predictor of execution time and maximum kicking velocity, but not for the total performance time and generated ground reaction forces. This article shows that kicking performance in taekwondo is affected by age and emphasises the need to develop age-specific training routines to optimise both performance and athletes` safety.